Contracting the difference? An initial cost-effectiveness assessment of Contracts for Difference for renewable energy deployment - Skoczylas,Maximilian Alexander (IIIEE Master Thesis, 2025)
Power sector decarbonisation is crucial for meeting global climate targets under the Paris Agreement as well as ensuring sustainable growth. Electricity and heat account for approximately 40% of energy‐related emissions and demand is only expected to increase, facilitating low‐carbon transitions in other sectors, from transport to industry. In response to the limitations of feed-in tariffs and renewable portfolio standards, two-way Contracts for Difference (CfDs) have emerged as the EU’s instrument of choice for stabilising electricity prices and accelerating renewable deployment. Yet despite the UK’s pioneering CFD scheme, operational since 2013, ex-post evaluations of the policy’s cost-effectiveness remain sparse. This study conducts a quantitative evaluation of the cost-effectiveness of CfDs in the UK context. The analysis explores the effect of CfD implementation in Wales on the installed capacity of renewable energy planning applications. I employ a difference-in-differences (DiD) study design, using Northern Ireland as a counterfactual to estimate the additional effect of CfD implementation. Combining estimates with financial analysis, I generate cost-effectiveness estimates for the CfD scheme in Wales for both total generation of awarded contracts and estimated additional generation. The estimated cost-effectiveness of CfDs in Wales was calculated at between £12/MWh-£49/MWh. The results of the DiD analysis reveal that up to 74% of contracted renewable capacity may have proceeded regardless of CfDs, driven by declining technology costs and favourable economic conditions, underlining the importance of counterfactual methods for accurate additionality assessment. Moreover, statistical tests detect no significant increase in installed capacity in Wales attributable to CfDs, a result potentially reflecting low statistical power of the sample and regional infrastructure limitations. Comparative review suggests that CfDs can equal or exceed the cost-effectiveness of other instruments, but heterogeneity in cost scopes and discount-rate assumptions across studies complicates direct comparison.
Keywords: renewable energy; contracts for difference; power sector; decarbonisation; cost; effectiveness; cost-effectiveness; difference-in-differences; United Kingdom; policy evaluation